Colon cancer presenting as a hepatic mass in pregnancy: A case report and review of the literature - Emeka Orie; Nnabuike Ngene; Thinagrin Naidoo; Jagidesa Moodley (South African Medical Association, 2014)
The incidences of hepatic masses and colon cancer in pregnancy are low. The clinical features of each can mimic those of pregnancy, thereby posing a diagnostic challenge to clinicians, particularly when the clinical scenario is complicated by HIV infection. This report illustrates such diagnostic difficulties, and the need to offer diagnostic colonoscopy to HIV-infected pregnant women who present with both a hepatic mass and minor gastrointestinal symptoms. It also highlights an approach to the management of colon carcinoma presenting as a hepatic mass in pregnancy.